2013
DOI: 10.1097/prs.0b013e3182729cc6
|View full text |Cite
|
Sign up to set email alerts
|

Grading Lipoaspirate

Abstract: Greater percentages of highest density fractions of lipoaspirate persist over time compared with lowest density fractions. A vasculogenic mechanism appears to contribute significantly, as highest density fractions contain more progenitor cells and increased concentrations of several vasculogenic mediators than lowest density fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…36,60 Furthermore, injection of high-density fat into FVB/NJ immunocompetent mice resulted in the largest fat graft 2 and 10 weeks after transplantation. 61 Histologic assessment of the fat graft formed with high-density fat demonstrated an increased number endothelial cells, a reduced number of collagen bands, and decreased fibrosis. These results correlated with increased expression of angiogenic factors such as vascular endothelial growth factor, stromal derived factor 1-alpha, platelet-derived growth factor, and adiponectin.…”
Section: Density Of Processed Tissuementioning
confidence: 95%
“…36,60 Furthermore, injection of high-density fat into FVB/NJ immunocompetent mice resulted in the largest fat graft 2 and 10 weeks after transplantation. 61 Histologic assessment of the fat graft formed with high-density fat demonstrated an increased number endothelial cells, a reduced number of collagen bands, and decreased fibrosis. These results correlated with increased expression of angiogenic factors such as vascular endothelial growth factor, stromal derived factor 1-alpha, platelet-derived growth factor, and adiponectin.…”
Section: Density Of Processed Tissuementioning
confidence: 95%
“…After harvesting, the lipoaspirate was enriched with stem cells through centrifugation. Our group and others have demonstrated that centrifugation at 3000rpm for 3 mins of the adipose tissue enriches fat with ADSC’s in the distal portion of the lipoaspirate [2729]. The proximal lipoaspirate graft was discarded along with the free oil and blood segments and only the distal lipoaspirate graft was used for injections.…”
Section: Methodsmentioning
confidence: 99%
“…5.5 A graded density of fat can be obtained by centrifuging the products of liposuction using standard Coleman technology ( Allen et al, 2013 ). Compared with the fat in the upper liposuction, the fat in the lower liposuction contains more ECM and ASCs, and higher concentrations of anti-inflammatory and fat angiogenesis factors ( Qiu et al, 2016 ; De Francesco et al, 2017 ).…”
Section: Clinical Avoidance Of Poor Extracellular Matrix Remodeling After Graftingmentioning
confidence: 99%